City of Boston Department of Parks, Twelfth Annual Report of Board of Commissioners for 1886, at 86 (1887) - (:unkn) unknown (My University, 1887)
§ 3: Prohibits the discharge or carry of firearms. Also prohibited the discharge of fireworks, playing of musical instruments, possession of intoxicating beverages, "or otherwise annoy other visitors" within the parks of Boston.
Keywords: CARRY - CERTAIN PUBLIC PLACES; DISCHARGE